2016
DOI: 10.1080/10408444.2016.1174669
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of the F344 rat as a cancer bioassay model (a retrospective summary of three common F344 rat neoplasms)

Abstract: The Fischer 344 (F344) rat was used by the National Toxicology Program (NTP) for over 5 decades for toxicity and carcinogenicity studies. However, in 2006, the NTP decided to switch to a different rat stock due largely to high background control incidences of Leydig cell tumors (LCTs) and mononuclear cell leukemia (MNCL), also known as large granular lymphocytic (LGL) leukemia. In the current review, we aim (1) to provide a summary of NTP bioassays with treatment-associated effects involving MNCL and LCTs in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 162 publications
0
29
0
1
Order By: Relevance
“…Since the incidence of large granular lymphocytic type leukemia was found to be within the historical control range and given that noting that the presence of this neoplasm is now interpreted quite differently (Thomas et al, 2007) than at the time of the Toyoda et al (1997), there is no indication of a treatment-related effect. In addition, as recently discussed by Maronpot et al (2016), this neoplasm is a result of the species-strain specific biology of the F344 rat and is of little relevance to human risk assessment. As such it could be argued that in reality the top dose of 5% in the study was the true NOAEL, which equates to a dose level of 1,997 mg/kg bw/d in males and 2,387 mg/kg bw/d in females.…”
Section: Discussionmentioning
confidence: 99%
“…Since the incidence of large granular lymphocytic type leukemia was found to be within the historical control range and given that noting that the presence of this neoplasm is now interpreted quite differently (Thomas et al, 2007) than at the time of the Toyoda et al (1997), there is no indication of a treatment-related effect. In addition, as recently discussed by Maronpot et al (2016), this neoplasm is a result of the species-strain specific biology of the F344 rat and is of little relevance to human risk assessment. As such it could be argued that in reality the top dose of 5% in the study was the true NOAEL, which equates to a dose level of 1,997 mg/kg bw/d in males and 2,387 mg/kg bw/d in females.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous mesothelioma is a rare neoplasm in rats with an incidence of 0.2 – 5%, the highest frequencies of which are reported in the Fischer 344 (F344) rat strain. Rat mesotheliomas typically occur in aged male rats and originate from the tunica vaginalis with the potential to spread into the peritoneal cavity via transcoelomic extension or seeding; primary intrathoracic mesotheliomas are rare (Hall 1990, Boorman et al 1990, Percy and Barthold 2007, Maronpot et al 2009, Maronpot et al 2016, Creasy et al 2012). To date, 17 studies from the NTP have reported xenobiotic-induced mesotheliomas in F344 rats; the F344 rat is particularly sensitive to developing this tumor type and is the only rodent strain reported to develop mesothelioma following xenobiotic exposure by a route other than peritoneal injection (Maronpot et al 2009, Maronpot et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Rat mesotheliomas typically occur in aged male rats and originate from the tunica vaginalis with the potential to spread into the peritoneal cavity via transcoelomic extension or seeding; primary intrathoracic mesotheliomas are rare (Hall 1990, Boorman et al 1990, Percy and Barthold 2007, Maronpot et al 2009, Maronpot et al 2016, Creasy et al 2012). To date, 17 studies from the NTP have reported xenobiotic-induced mesotheliomas in F344 rats; the F344 rat is particularly sensitive to developing this tumor type and is the only rodent strain reported to develop mesothelioma following xenobiotic exposure by a route other than peritoneal injection (Maronpot et al 2009, Maronpot et al 2016). Histologically, mesotheliomas may be difficult to distinguish from mesothelial hyperplasia as they can range from a single layer of hyperplastic mesothelial cells lining a thin fibrovascular stroma to papillary projections lined by multiple, irregular layers of cuboidal to polygonal cells that form a pavement or stratified pattern (Hall 1990, Boorman et al 1990, Percy and Barthold 2007, Maronpot et al 2009, Maronpot et al 2016, Creasy et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations